Validity of coital diaries in a feasibility study for the Microbicides Development Programme trial among women at high risk of HIV/AIDS in Mwanza, Tanzania. Issue 6 (27th July 2007) - Allen, Caroline F; Lees, Shelley S; Desmond, Nicola A; Der, Geoff; Chiduo, Betty; Hambleton, Ian; Knight, Louise; Vallely, Andrew; Ross, David A; Hayes, Richard J
Abstract : Objectives: To compare coital diaries and face-to-face interviews (FFIs) in measuring sexual behaviour among women at high risk of HIV. To assess the effect of differing levels of support from researchers on reporting in coital diaries and FFIs. Methods: Three groups of 50 women were randomly selected from a cohort of food and recreational facility workers participating in a microbicide trial feasibility study and received differing levels of researcher support. Minimum support involved delivering and collecting coital diaries weekly; medium support included a weekly FFI and discussion of concerns; intensive support also included an unscheduled mid-week visit when diaries were checked and concerns addressed. All respondents participated in an exit FFI, including questions on sexual behaviour over the four-week study period and study acceptability. Results: Sexual behaviours were generally reported more frequently in coital diaries than weekly or exit interviews. Vaginal and anal sex, male and female condom use, vaginal cleaning and lubrication, sex during menstruation and sex with irregular and regular partners were reported more frequently in coital diaries than exit interviews. In coital diaries, level of support was associated with reporting of vaginal sex and cleaning. In exit interviews, support level was associated with reporting of vaginal sex, vaginal cleaning and sex with regular, irregular and commercial partners. Women with minimum support reported least satisfaction with the research process. Women with intensive support were most likely to report that they informed someone about their study participation and that they completed diaries daily. Conclusion: Compared with FFIs, coital diaries resulted in higher reporting of socially stigmatised activities, and sexual behaviour reporting varied less by level of support. More researcher support enhanced study acceptability.